A DISCOURSE ANALYSIS THROUGH CORPUS LINGUISTICS ON THE CASE OF POPULAR SCIENCE BOOK THE GRAND DESIGN - Uyun, Rosita Masfirotul (Universitas Muhammadiyah Surakarta, 2016)
This study aims to discover the theme of popular physics book, The GrandDesign, through corpus linguistics and discourse analysis as well as how theauthors of the book describe the field of study which in fact is not their mainfocus to work on. In this case, the authors are physicists and cosmologists whoattempt to use quantum to interpret the history if the universe. There were twoterms, quantum and cosmology, which would be examined to gain the number ofappearance in the book. A computer-based corpus software, AntConc v 3.4.3w andchi square test were employed to gain the hit numbers and the significant value ofthe possible different number appeared. This result would answer the question ofwhat the theme of the book is. The procedure of corpus analysis, which raw textis directly analyzed, was used along with collocation and concordance analysis.After the data was gained from collocation and concordance analysis, discourseanalysis was applied to obtain the profound findings of how the authors asserttheir opinion of quantum in the study of the cosmology. This paper resulted thatquantum has more hit numbers than cosmology. In addition, it was found thatthe theory proposed in this book was quite inadequate in a certain circumstance.